Psychology journals guidelines on title, abstract and keywords - Terra, Ana Lúcia (2022)
The aim of this exploratory study on the wording of the title, abstract and keywords of the articles is to verify and analyze the author’s guidelines in scientific journals of Psychology. The method used a combination of quantitative and qualitative techniques applied in a representative sample of journals in the area of Psychology indexed in the Journal Citation Reports (JCR), considering the first eight titles of each of the four quartiles. The sample consisted of 32 magazines out of 77 (41.5%). A pre-adapted and tested spreadsheet was used. Data collection and processing was carried out on 38 items grouped into categories related to identification data, title guidelines, summary and keywords of the scientific article. The results reveal that the 32 magazine titles belong to 11 different publishers; all have some kind of style manual with guidelines that vary between complete and more superficial. Most have guidelines for drafting the title (75%, n. 24), abstract (96.8%, n. 31) and keywords (71.8% n. 23). The use of graphic and video abstracts are highlighted as new ways to disseminate the content of scientific articles. It is concluded that these aspects are aligned to a greater or lesser degree with the guidelines of the ISO standard and the APA manual. However, they are more related to the protocols of editorial management procedures for the dissemination of scientific work in a digital environment than to the intrinsic quality of documentary products associated with the organization and representation of Science.